A bright future for the library and library professional / Nur Afeqah Abdullah and Nur Syafiqah Hassan - Abdullah, Nur Afeqah; Hassan, Nur Syafiqah (2020)
The purpose of this paper is to explore the future vision of library and librarians in the new technology demand referring new user needs, new skills for staff and services offered. The literature reveals that transformation of new technologies giving an implicationtowards library staff, library services and future user demands.It also shows that communities are still relyingon libraries for a variety of services and activities. Hence, the needs for librarians to manage libraries and help users to search information arestill relevant. The deliberations in this paper are surrounded by conceptualization of what the library products, services and librarians'roleswill be in future libraries. Further studies are needed to investigate the opportunities and possibility for professional librarians and library to enhance their roles facing new era IR 4.0.